Globalization, trade liberalization and poverty alleviation in southeast Asia: The case of the livestock sector in Vietnam - Nin-Pratt, Alejandro; Lapar, Ma. Lucila; Ehui, Simeon K. (2003)
A number of developing countries consider their livestock production sectors to be particularly vulnerable to global trade liberalization, especially because of the dominance of smallholder systems. The argument goes that agricultural trade liberalization will give undue advantage to large-scale commercial livestock systems at the expense of smallholder production systems, and that this in turn will add to the adjustment pressures on smallholder producers for whom income from livestock production is vital in helping them avoid poverty. We use a micromacro approach that combines the GTAP general equilibrium model with a simple micro model to measure expected impacts of trade liberalization on a representative sample of Vietnam\92s livestock producers. Our results show that the impact of trade liberalization on Vietnam\92s livestock production tends to be small but in general a more open Vietnamese economy would result in a deterioration of the trade balance of livestock products. In spite of this, trade liberalization would benefit poor livestock producers by increasing livestock prices relative to production costs, in particular feed costs, and by increasing non-agricultural income.